Metabotropic glutamate receptor 5 ablation accelerates age-related neurodegeneration and neuroinflammation. (June 2019) - Carvalho, Toniana G.; Alves-Silva, Juliana; de Souza, Jessica M.; Real, Ana L.C.V.; Doria, Juliana G.; Vieira, Erica L.M.; Gomes, Giovanni F.; de Oliveira, Antonio C.; Miranda, Aline S.; Ribeiro, Fabiola M.
Abstract: The growing elderly population world widely prompts the need for studies regarding aged brain and its susceptibility to neurodegenerative diseases. It has been shown that aged brain exhibits several alterations, including neuroinflammation, which prone this organ to neurodegenerative processes. Metabotropic glutamate receptor 5 (mGlu5 receptor) has a role in neuronal cell loss and inflammation. Although the relevance of mGlu5 receptor in different diseases has been investigated, its involvement in normal brain aging remains unclear. In the present study, we used the mGlu5 receptor knockout (mGluR5 −/− ) mice, a model of Huntington's Disease (BACHD), and the double mutant mice (mGluR5 −/− /BACHD), at the ages of 2, 6 and 12 months, to investigate whether mGlu5 receptor has a role in brain aging. We demonstrated that mGluR5 −/− mice exhibit diminished number of neurons at 12 months of age in the cortex and striatum, similarly to what was observed in the case of BACHD and mGluR5 −/− /BACHD mice. In addition, ablation of mGlu5 receptor increased the number of astrocytes and microglia in BACHD and wild type (WT) mice in an age-dependent manner in the cortical region, but not in the striatum. Interestingly, 12-month-old mGluR5 −/− mice induced microglia activation, evidenced by increased CD68 expression and diminished number of microglia ramifications in skeleton analyses. Importantly, the presence of mutant huntingtin and the absence of mGlu5 receptor promoted decreased levels of fractalkine expression in aged mice, which could account for the decreased levels of microglia activation in these mice. Together, our data provide evidence that mGlu5 receptor plays a role in brain aging by modulating different cell types in the central nervous system (CNS). Highlights: mGluR5 −/− mice exhibit age-dependent neuronal cell loss to the same levels as that of a mouse model of Huntington's disease. mGlu5 receptor knockout triggers gliosis and microglia activation in the cortex in an age-dependent manner. The presence of htt and ablation of mGlu5 receptor decrease expression of fractalkine in aged mice.